Retrato del derecho operacional en Colombia desde la academia - Jesús E. Caldera Ynfante, Jean Carlo Mejía Azuero,; Jiménez Reina, Jonnathan (Opción, 2020)
El Derecho Operacional es una rama nueva de la ciencia jurídica que surge contemporáneamente como consecuencia de las metamorfosis que han suscitado a nivel socio-político. Adicionalmente, el Derecho Operacional (DOPER) se caracteriza por ser una herramienta trascendental que se encarga de entender e interpretar las acciones de las Fuerzas Militares y de la Policía Nacional de Colombia en materia operacional, en donde el fin último es comprender las actividades de la Fuerza Pública por medio de un marco jurídico especial, en el cual se entrecruzan preceptos expuestos en la Constitución Política de Colombia de 1991 junto con ordenamientos internacionales. Es menester mencionar que se deben analizar temas vinculados con los antecedentes y la trayectoria del D O actualidad, lo cual permite esclarecer el fundamento real del surgimiento de un concepto hoy avalado por la propia Corte Constitucional colombiana.  AbstracThe Operational Law is a new branch of legal science at the same time arising as a consequence of the metamorphosis that has occurred in a socio-political level. Additionally, the Operational Law stands out as a crucial tool that is responsible for guiding the Military Forces and Police Forces of Colombia to a scenario of post-agreement, in which the ultimate aim of these regulations is to supervise the activities of the Public Force by means of a special legal framework which intersect the statutes set out in the Colombian Political Constitution of 1991 together with international norms. This has as its main objective to preserve a fair, secure and peaceful world governed by the rule of law. To achieve such a goal the UN encourages and promotes establishing rules exposed in the manuals of international law, which will play an important role during the exercise of the Operational Law. It is necessary to mention that, for writing an upstanding State-of-the-Art subject related to the history and trajectory of the concept must be exposed, therefore historical and actual themes that allow clarifying the true idea of the rise of the term of  O           L w                      C              C        Colombia